Influence of substrate density and cropping conditions on the cultivatioof sun mushroom - Pardo-Giménez, Arturo; Carrasco, Jaime; Pardo, Jose E.; Álvarez-Ortí, Manuel; Zied, Diego C. [UNESP] (My University, 2020)
Aim of study: To evaluate agronomical features demanded by the sun mushroom (Agaricus subrufescens) in order to optimise the commercial cultivation of this worldwide demanded medicinal mushroom. Area of study: The study was carried out in Castilla-La Mancha (Spain), the second most productive region of cultivated mushrooms in Spain. Material and methods: In this work we summarise the results obtained while evaluating the performance of sun mushroom crops (A. subrufescens). Two agronomical traits have been evaluated, the effect on the productive outputs of applying five different compost filling rates of high N substrate (yield and BE of the compost), and the influence of implementing two different conditions for the induction to fructification on the analytical properties of the harvested mushrooms. Besides, two commercial compost formulations (CM and VC) obtained from local providers have been used. Main results: The number of sporophores harvested and the yield per unit area increased with rising density of compost load, although the biological efficiency was not significantly modified. Compost fill rate of 70 kg m-2 provided an average yield of 13.33 kg m-2 and BE=55.45 kg dt-1, generally higher than those values reported in the literature. The proposed moderate slow induction provides better yields, particularly in the last flushes, and larger sporophores. Proximate analysis of harvested sporophores has not shown significant differences between treatments or factors. Research highlights: As guidance for growers, compost fill weight between 65 and 70 kg per m2 of productive area with a moderate slow induction to fructification is presented as the best option for commercial production under controlled environmental conditions.
Keywords: Agaricus subrufescens; Agronomic performance; Compost filling rate; Medicinal mushroom; Proximate analysis